Sample preparation and UHPLC-FD analysis of pteridines in human urine - Tomšíková, H; Solich, P; Nováková, L (Journal of pharmaceutical and biomedical analysis, 2014)
Elevated levels of pteridines can indicate the activation of cellular immune system by certain diseases. No work dealing with the simultaneous determination of urinary neopterin, biopterin and their reduced forms has been published. Therefore, a new SPE-UHPLC-FD method for the analysis of these compounds has been developed. The main emphasis was put on the stability of dihydroforms during the sample processing and storage. As a stabilizing agent, dithiothreitol, at various concentrations, and various pH values (3.8-9.8) of working solutions were tested. Chromatographic separation was performed under HILIC isocratic conditions on BEH Amide column. The method was linear for the calibration standard solutions in the range of 10-10,000 ng/ml (dihydroforms) and 0.5-1000 ng/ml (oxidized forms), and for real samples in the range of 25-1000 ng/ml (dihydroforms) and 1-100 ng/ml (oxidized forms). The development of a new SPE sample preparation method was carried out on different types of sorbents (based on a mixed-mode cation exchange, porous graphitic carbon and a polymer comprising hydrophilic and hydrophobic components). Final validation was performed on a MCAX SPE column. Method accuracy ranged from 76.9 to 121.9%. The intra- and inter-day precision did not exceed 10.7%. The method provided high sensitivity for the use in routine clinical measurements of urine (LLOQ 1 ng/ml for oxidized forms and 25 ng/ml for dihydroforms). Average concentrations of biopterin, neopterin, and dihydrobiopterin found in urine of healthy persons were related to the mol of creatinine (66.8, 142.3, and 257.3 μmol/mol of creatinine, respectively) which corresponded to the literature data. The concentration of dihydroneopterin obtained using our method was 98.8 μmol/mol of creatinine.
Keywords: stabilita léku; Solid Phase Extraction; UHPLC-FD; Neopterin; Hydrogen-Ion Concentration; Pteridines; dithiothreitol; Biopterin; vysokoúčinná kapalinová chromatografie; lidé; Drug Stability; Dithiothreitol; pteridiny; Chromatography, High Pressure Liquid; extrakce na pevné fázi; Dihydroforms; koncentrace vodíkových iontů; SPE; Humans